The riviera house eaudiobook - Lester, Natasha (2021)
A lush and engrossing novel of one woman's quest to keep Nazis from stealing priceless art during WWII, perfect for fans of The Rose Code. Paris, 1939: The Nazis think Éliane can't understand German. They're wrong. They think she's merely cataloging art in a Louvre museum and unaware they're stealing national treasures for their private collections. They have no idea she's carefully decoding their notes and smuggling information to the Resistance. But Éliane is playing a dangerous game. Does she dare trust the man she once loved with her secrets, or will he only betray her once again? She has no way to know for certain . . . until a trip to a stunning home on the French Riviera brings a whole new level of peril. Present Day: Wanting to forget the tragedy that has left her life in shambles, Remy Lang heads to a home she's mysteriously inherited on the Riviera. While working on her vintage fashion business, she discovers a catalog of the artworks stolen during World War II and is shocked to see a painting that hung on her childhood bedroom wall. Who is her family, really? And does the Riviera house hold more secrets than Remy is ready to face?